Hepatoid adenocarcinoma of the stomach with metastatic choriocarcinoma of the liver: A case report of a rare subtype of gastric cancer with a complex treatment course - Zhou, Qiyang; Zhou, Yudi; Ouyang, Yiming; Chen, Weichang; Zhou, Xiaojun (Frontiers in Surgery, 2022)
Abstract Gastric hepatoid adenocarcinoma and hepatic choriocarcinoma are rare diseases in clinical settings, and the case we report here is a combination of both. A 66-year-old woman presented with a chief complaint of abdominal discomfort. The patient was examined using gastroscopy and computed tomography (CT) scan, and these revealed an irregular surface ulcer on the wall of the gastric antrum. A mass, 2.0 cm in diameter, was found in the liver in April 2020. The endoscopic biopsy findings were consistent with a diagnosis of moderately-poorly differentiated hepatoid adenocarcinoma. She was then referred to our hospital for further treatment. Initially, neoadjuvant therapy was initiated for the patient. The CT scan showed that the liver metastases had progressed; hence, surgery was performed. Postoperative pathology showed that the gastric lesions were mostly hepatoid adenocarcinoma with no choriocarcinoma, while the liver lesions comprised about 10% hepatoid adenocarcinoma and 90% choriocarcinoma. One month later, the patient developed tumor recurrence in the liver as observed on CT imaging. Subsequently, a variety of chemotherapy regimens were tried with no obvious results. The patient eventually developed multiple organ metastasis, and died in July 2021. The overall survival was 16 months. Based on findings from this case report it appears that initial neoadjuvant therapy was not effective and radical surgery may be the best treatment for patients with HAS.